What is artificial intelligence? - Loukides, Michael Kosta; Lorica, Ben (O'Reilly Media, 2016)
From computer vision to game playing, artificial intelligence (AI) has made a lot of progress in the past few years. Companies such as Google and Facebook have already placed huge bets on this technology, and over the next decade, AI features will steadily creep into one product after another. In this O'Reilly report, you'll examine the state of AI today and where we might be headed in coming years. To explain today's AI capabilities, authors Ben Lorica and Mike Loukides look at prominent examples such as Google's AlphaGo, self-driving cars, and face recognition--AIs that consist of narrow solutions to specific problems. Can researchers develop general intelligence flexible enough for an AI to learn without supervision, or choose what it wants to learn? This report takes a deeper look into: The meaning of "general intelligence" when applied to AIs Moving AIs from supervised learning to unsupervised learning Why AIs can easily solve problems that humans find challenging, but not problems that humans find easy The differences between autonomous AIs and assistive AIs that augment our intelligence Factors that have made AI a hot topic in recent years Today's successful AI systems, such as machine learning and computer vision OpenAI and the push to make AI research open and visible to the public